Technical note: Chemical composition and source identification of fluorescent components in atmospheric water-soluble brown carbon by excitation–emission matrix spectroscopy with parallel factor analysis – potential limitations and applications - T. Cao; T. Cao; T. Cao; M. Li; M. Li; M. Li; C. Xu; C. Xu; C. Xu; J. Song; J. Song; J. Song; et al. (Atmospheric Chemistry and Physics, 2023)
Three-dimensional excitation–emission matrix (EEM) fluorescence spectroscopy is an important method for the identification of the occurrence, chemical composition, and source of atmospheric chromophores. However, current knowledge on the identification and interpretation of fluorescent components is mainly based on aquatic dissolved organic matter and might not be applicable to atmospheric samples. Therefore, this study comprehensively investigated EEM data of different types of strong light-absorbing organic compounds, water-soluble organic matter (WSOM) in different aerosol samples (combustion source samples and ambient aerosols), soil dust, and purified fulvic and humic acids supplemented by parallel factor (PARAFAC) modeling. The results demonstrated that organic compounds with high aromaticity and strong electron-donating groups generally present strong fluorescence spectra at longer emission wavelengths, whereas organic compounds substituted with electron-withdrawing groups have relatively weaker fluorescence intensity. In particular, aromatic compounds containing nitro groups (i.e., nitrophenols), which show strong absorption and are the major component of atmospheric brown carbon, exhibited no significant fluorescence. The EEM–PARAFAC method identified three fluorescent components (i.e., C1, C2, and C3) in ambient WSOM. Although EEM–PARAFAC-derived C1 (Ex/<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1b4178c77ca0d4bfee6c9ddd864f3a43"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-2613-2023-ie00001.svg" width="8pt" height="14pt" src="acp-23-2613-2023-ie00001.png"/></svg:svg>Em = 235, 270/330<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="45pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="4095a45018ee4f06801f0232da2e1364"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-2613-2023-ie00002.svg" width="45pt" height="14pt" src="acp-23-2613-2023-ie00002.png"/></svg:svg> nm) in ambient WSOM is generally considered to be protein-like groups, our findings suggested that it is mainly composed of aromatic acids, phenolic compounds, and their derivatives, with only traces of amino acids. C2 is associated with the atmospheric chemical reaction of biomass burning and/or biogenic organic molecules, with a relatively lower degree of oxidation, which are more abundant in Guangzhou WSOM (56 %–69 %). C3, in contrast, is mainly attributed to highly oxygenated organic molecules derived from soil and atmospheric aging processes and has a relatively higher contribution in Chuzhou WSOM (23 %). These findings provide new insights into the analysis of chemical properties and sources of atmospheric fluorophores using the EEM method.